7075 aluminum alloy composite powder and laser selective melting forming method

CN117920990BActive Publication Date: 2026-10-23FUJIAN UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410233862.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-01
Publication Date
2026-10-23
Estimated Expiration
2044-03-01

AI Technical Summary

Technical Problem

[0003]但是,由于7075铝合金的较差的焊接性能、较低的激光吸收率和较高热裂纹敏感性,导致SLM制备的7075铝合金样件出现热裂纹,成型效果差,样件受到裂纹和孔洞缺陷的影响,力学性能表现较差,不能满足工业应用的要求,裂纹缺陷不能通过调整工艺参数消除

Benefits of technology

与现有技术相比,本发明所采用的形核剂实心球形Ti粉和Ta颗粒,在打印过程中除了会原位产生Al3X沉淀相,并且还能产生Ti19Ta纳米粒子,实现晶粒细化,消除热裂纹的同时提高了7075铝合金的耐腐蚀性。试验结果表示添加Ti和Ta双形核剂颗粒的样件比添加单形核剂的样件力学性能和耐腐蚀性均有明显提高。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117920990B_ABST
    Figure CN117920990B_ABST
Patent Text Reader

Abstract

The application provides a 7075 aluminum alloy composite powder and a laser selective melting forming method. Components of the 7075 aluminum alloy composite powder are as follows in terms of mass percentage: 1.0-2.0 wt.% Ti powder, 1.0-2.0 wt.% Ta powder, and the balance of 7075 aluminum alloy powder. The nucleating agent solid spherical Ti powder and Ta particles used in the application realize grain refinement, eliminate thermal cracks, and improve the corrosion resistance of the 7075 aluminum alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of metal additive manufacturing technology, specifically to a 7075 aluminum alloy composite powder and a laser selective melting forming method. Background Technology

[0002] Selective laser melting (SLM) is an advanced additive manufacturing (AM) technology, also known as metal 3D printing. It uses a high-energy laser beam to melt metal powder layer by layer to build three-dimensional objects. It can create complex three-dimensional structures, including internal cavities, threads, and mesh structures, without the need for traditional machining molds. Because it can manufacture complex integral parts in a single operation, it reduces subsequent assembly processes and shortens part manufacturing time. Compared to traditional machining methods, SLM can improve raw material utilization. 7075 high-strength aluminum alloy has high specific strength, excellent mechanical properties, and machinability, and is widely used in aerospace, transportation, and military equipment.

[0003] However, due to the poor weldability, low laser absorption rate, and high hot cracking sensitivity of 7075 aluminum alloy, hot cracking occurs in 7075 aluminum alloy samples prepared by selective laser melting (SLM), resulting in poor forming effect. The samples are affected by cracks and voids, leading to poor mechanical properties that fail to meet industrial application requirements. Furthermore, these crack defects cannot be eliminated by adjusting process parameters. The main objective of this invention is to provide a composite powder, preparation method, and heat treatment process capable of eliminating the defects in 7075 aluminum alloy formed by selective laser melting. Summary of the Invention

[0004] This invention provides a 7075 aluminum alloy composite powder formulation and a laser selective melting forming method.

[0005] The growth-limiting ability of segregating elements can slow down the rate of solid-liquid interface advancement during laser selective melting, allowing for more grain nucleation and enhancing grain strengthening. The growth-limiting ability of typical elements in aluminum alloys on grains at the solid-liquid interface front can be quantified using the growth restriction factor (GFR). In the formula: m is the slope of the liquidus line; k is the solute partition coefficient; C0 is the solute concentration in the alloy. As shown in Table 1, Ti has a strong growth-limiting effect compared to other elements.

[0006] Table 1. Growth-limiting effects of typical segregating elements in aluminum alloys Tantalum has extremely high corrosion resistance and does not react with hydrochloric acid, concentrated nitric acid, or aqua regia under both cold and hot conditions. Below 150°C, tantalum is not corroded by concentrated sulfuric acid; it only reacts above this temperature. In concentrated sulfuric acid at 175°C for one year, the corrosion thickness is 0.0004 mm. Immersing tantalum in sulfuric acid at 200°C for one year results in only 0.006 mm of surface damage.

[0007] Therefore, adding titanium nucleating agents alone cannot improve the corrosion resistance of 7075 aluminum alloy, and adding tantalum nucleating agents alone does not have the same grain refinement effect as adding titanium particles. The molten pool temperature ranges from 100 to 3000℃. Adding either Ti or Ta alone only forms Al3X as a precipitate phase. However, when Ti and Ta particles are added simultaneously, Al3Ti and Al3Ta can be formed in situ at a molten pool temperature of 600–800℃. At a molten pool temperature of 1000–1700℃, the molten Ti will surround the Ta particles to form TiO2. 19 Ta has a significant effect on grain refinement, while Ti 19 Ta can improve the corrosion resistance of 7075 aluminum alloy. Therefore, this invention proposes a method to simultaneously add Ti and Ta particles as nucleating agents, which refines the grain size while improving the corrosion resistance of 7075 aluminum alloy.

[0008] This invention prepares crack-free 7075 aluminum alloy samples by optimizing the alloy formula and adding reinforcing phase particles to 7075 aluminum alloy powder. After appropriate heat treatment, the tensile properties and elongation can be effectively improved, making the mechanical properties comparable to those of traditional cast 7075 aluminum alloy.

[0009] The present invention adopts the following technical solution: The composition of the 7075 aluminum alloy composite powder, by mass percentage, is: 1.0–2.0 wt.% Ti powder, 1.0–2.0 wt.% Ta powder, and the balance being 7075 aluminum alloy powder. This invention also proposes a preparation method and a forming method for the above-mentioned composite powder, wherein the preparation and forming methods include: (1) Weigh out the corresponding mass of Ti powder, Ta powder and 7075 aluminum alloy powder according to the proportion; (2) Mix the three powders in a grinding mill; (3) Place the composite powder obtained in step (2) into a drying oven and dry it; (4) Place the dried composite powder from step (3) into a metal additive manufacturing equipment to form a sample; (5) Heat treatment is performed on the molded sample obtained in step (4).

[0010] (6) Conduct an electrochemical corrosion test on the sample after heat treatment in step (5).

[0011] In step (1), the 7075 powder is solid spherical with a particle size of 15-53 mm; the Ti powder particles are solid spherical with a particle size of 5-25 mm. In step (2), the mill speed is 70-90 rpm, and the milling time is 6 hours. Vibrate the powder jar for 10-15 minutes every 1-2 hours.

[0012] In step (3), the drying oven is evacuated, the drying temperature is 60℃~80℃, and the drying time is 3~6 hours; In step (4), the forming process parameters are as follows: the laser power is 240-300W, the corresponding composite powder forming temperature can reach 1000-3000℃, the scanning speed is 500-700mm / s, the scanning distance is 80-110mm, the powder thickness is 20-30mm, the substrate is an aluminum alloy substrate, the substrate preheating temperature is 180-200℃, the scanning angle of adjacent powder layers is rotated by 67°, the forming chamber uses argon gas, and the oxygen content is less than 100ppm.

[0013] The heat treatment process in step (5) consists of strengthening solution treatment and reversion aging treatment. Strengthening solution treatment: 460℃~490℃, holding for 60~90min, then heating at 5-10℃ / h to 480~510℃, water quenching to room temperature, transfer time <10s; pre-aging temperature 115~125℃. Aging time is 20~24h. Reversion aging temperature 150~200℃. Aging time is 20~24h. Re-aging temperature 115~125℃. Aging time is 20~24h.

[0014] The advantages of this invention are: Compared with existing technologies, the solid spherical Ti powder and Ta particles used in this invention, in addition to generating Al3X precipitate in situ during the printing process, can also generate Ti. 19 Ta nanoparticles refine the grains, eliminating hot cracks while improving the corrosion resistance of 7075 aluminum alloy. Experimental results show that samples with both Ti and Ta nucleating agent particles exhibit significantly improved mechanical properties and corrosion resistance compared to samples with only a nucleating agent.

[0015] Existing methods for mixing powders commonly use low-energy ball milling. The stainless steel or agate balls used in these methods can break up the spherical aluminum alloy powder during mixing, compromising the sphericity of the composite powder and affecting its flowability. If the reinforcing phase particles are not spherical, they will combine with the spherical aluminum alloy particles during mixing, forming irregular particles, which also affects the flowability of the composite powder. If the particle size of the reinforcing phase is too small, within the nanometer range, it will adhere to the walls of the ball mill jar and the conveying pipes of the forming equipment during mixing and preparation, resulting in the final composite powder having a lower than expected proportion of the reinforcing phase.

[0016] 7075 aluminum alloy, as a heat-treatable alloy, is traditionally treated with solution treatment and aging treatment. Compared to single-stage solution treatment, the strengthening solution treatment used in this invention can maximize the alloy's solid solubility and achieve a more saturated solid solution state. While ordinary single-stage aging treatment, i.e., T6 heat treatment, can improve the strength of the aluminum alloy to some extent, it significantly reduces the alloy's corrosion resistance. Therefore, some researchers have used two-stage aging to improve the corrosion resistance, but this has resulted in a decrease in strength. Therefore, this invention proposes a regression aging heat treatment process that can maintain high strength while providing high corrosion resistance to the aluminum alloy. Attached Figure Description

[0017] Figure 1 The following are scanning electron microscope (SEM) images of the particle size and shape of the three powders used in this invention: (a) SEM image of 7075 aluminum alloy powder, (b) SEM image of Ti powder particles, (c) SEM image of Ta powder particles, and (d) SEM image of (Ti+Ta) / 7075 aluminum alloy composite powder. Figure 2 This is a particle size distribution diagram of 7075 aluminum alloy powder; Figure 3 This is a microstructure diagram of the laser selective melting forming sample of Embodiment 1 of the present invention; Figure 4 This is a microstructure diagram of the laser selective melting forming sample of Comparative Example 1 of the present invention; Figure 5 This is a microstructure diagram of the laser selective melting forming sample of Comparative Example 2 of the present invention; Figure 6 This is a microstructure diagram of the laser selective melting forming sample of Comparative Example 3 of the present invention; Figure 7 Ti generated in Embodiment 1 of the present invention 19 XRD pattern of Ta nanoparticles. Detailed Implementation

[0018] To make the above features and advantages of the present invention more apparent and understandable, specific embodiments are provided below for detailed description. Unless otherwise specified, the methods of the present invention are conventional methods in the art.

[0019] The specific composition of the 7075 aluminum alloy powder used in the following examples and comparative examples is shown in the table below.

[0020] Table 2 Chemical composition of 7075 aluminum alloy powder (mass fraction / %) Example 1 S1. Weigh out three powders according to the ratio of 1.0 wt.%Ti + 1.0 wt.%Ta + 98.0 wt.%7075 aluminum alloy and set aside. S2. The mixed powder weighed in S1 is subjected to can milling at a mill speed of 80 rpm for 6 hours, with the powder can being vibrated for 10 minutes every hour. Then, the powder is dried in a vacuum oven at a temperature of 70°C for 6 hours.

[0021] S3. Laser selective melting and forming of the composite powder dried in S2: Forming process parameters: laser power is 270W, scanning speed is 600mm / s, scanning interval is 90mm, powder thickness is 30mm, substrate is aluminum alloy substrate, substrate preheating temperature is 200℃, adjacent powder layer scanning angle is rotated 67°, argon gas is used in the forming chamber, and oxygen content is less than 100ppm. S4. The printed part undergoes heat treatment to strengthen and solidify it. It is held at 470℃ for 60 minutes, then heated to 490℃ at a rate of 10℃ / h, and water-quenched to room temperature with a transfer time of <10s. The pre-aging temperature is 120℃. The aging time is 24 hours, followed by a re-aging at 170℃. The aging time is again 24 hours, with a second aging at 120℃ for a total aging time of 20 hours. The mechanical properties of the sample are: tensile strength of 542 MPa, elongation of 20.1%, corrosion voltage of -0.653V, and corrosion current density of 3.540 × 10⁻⁶. -6 A / cm 2 .

[0022] Comparative Example 1 S1. Weigh out two powders according to the ratio of 2.0 wt.%Ti + 98.0 wt.%7075 aluminum alloy and set aside for later use; S2. The mixed powder weighed in S1 is subjected to can milling at a mill speed of 80 rpm for 6 hours, with the powder can being vibrated for 10 minutes every hour. Then, the powder is dried in a vacuum oven at a temperature of 70°C for 6 hours.

[0023] S3. Laser selective melting and forming of the composite powder dried in S2: Forming process parameters: laser power 270W, scanning speed 600mm / s, scanning interval 90mm, powder thickness 30mm, aluminum alloy substrate, substrate preheating temperature 200℃, scanning angle rotation of adjacent powder layers 67°, argon gas in the forming chamber with an oxygen content of 100ppm, no heat treatment performed on the printed parts. Mechanical properties of the sample: tensile strength 458MPa, elongation 15.5%, corrosion voltage -0.733V, corrosion current density 3.929×10⁻⁶. -5 A / cm 2 .

[0024] Comparative Example 2 S1. Weigh out the two powders according to the ratio of 2.0 wt.%Ta + 98.0 wt.%7075 aluminum alloy and set aside. S2. The mixed powder weighed in S1 is subjected to can milling at a mill speed of 80 rpm for 6 hours, with the powder can being vibrated for 10 minutes every hour. Then, the powder is dried in a vacuum oven at a temperature of 70°C for 6 hours.

[0025] S3. Laser selective melting and forming of the composite powder dried in S2: Forming process parameters: laser power 270W, scanning speed 600mm / s, scanning interval 90mm, powder thickness 30mm, aluminum alloy substrate, substrate preheating temperature 200℃, scanning angle rotation of adjacent powder layers 67°, argon gas in the forming chamber, oxygen content 100ppm, no heat treatment performed on the printed parts. Mechanical properties of the sample: tensile strength 421MPa, elongation 17.9%, corrosion voltage -0.700V, corrosion current density 3.884×10⁻⁶. -6 A / cm 2 .

[0026] Comparative Example 3 S1. Weigh a certain amount of 7075 aluminum alloy raw powder for later use; S2. The 7075 aluminum alloy powder weighed in S1 is dried. The drying oven is evacuated, the drying temperature is 70℃, and the drying time is 6 hours. Then, laser selective melting is performed: forming process parameters: laser power is 270W, scanning speed is 600mm / s, scanning interval is 90mm, powder thickness is 30mm, the substrate is an aluminum alloy substrate, the substrate preheating temperature is 200℃, the scanning angle between adjacent powder layers is rotated by 67°, the forming chamber uses argon gas with an oxygen content of 100ppm, and no heat treatment is performed on the printed parts. Mechanical properties of the sample: tensile strength is 25MPa, elongation is 0.5%, corrosion voltage is -1.251V, and corrosion current density is 4.775×10⁻⁶. -4 A / cm 2 .

[0027] Particle size of 7075 aluminum alloy powder and electron micrographs of the three powders are shown below. Figure 1 and Figure 2 As shown, the sample prepared by selective laser melting in Example 1 has a density of 98.3%. Images of the sample surface were obtained using an optical microscope, as shown below. Figure 3 As shown, the sample surface has no thermal cracks, only a very small number of gas pores. The sample prepared by laser selective melting in Comparative Example 1 has a density of 97.6%, as shown in the figure. Figure 4As shown, large spherical pores exist on the sample surface. This is because the Ti powder particles contain a certain amount of oxygen, which escapes during the melting process. The sample prepared by laser selective melting in Comparative Example 2 has a density of 97.0%. Figure 5 As shown, the sample still has many fine cracks, and Ta powder particles are less effective than Ti powder particles in eliminating hot cracks. The sample prepared by laser selective melting in Comparative Example 3 has a density of 96.6%. Figure 6 As shown, due to the absence of a nucleating agent, numerous hot cracks and irregular pores were present on the sample surface. Tensile tests were conducted on samples from Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3, and the mechanical properties are shown in Table 3.

[0028] Table 3 Comprehensive Performance of Samples The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made within the scope of the claims of the present invention should be included in the scope of the present invention.

Claims

1. A laser selective melting forming method for 7075 aluminum alloy composite powder, characterized in that: The composition of the 7075 aluminum alloy composite powder by mass percentage is: 1.0 to 2.0 wt.% Ti powder, 1.0 to 2.0 wt.% Ta powder, and the balance is 7075 aluminum alloy powder; The 7075 aluminum alloy powder is solid spherical; the Ti powder particles are solid spherical; the Ta powder particles are solid spherical; The laser selective melting and shaping process includes the following steps: (1) Weigh out the corresponding mass of Ti powder, Ta powder and 7075 aluminum alloy powder according to the proportion; (2) Mix the three powders in a grinding mill; (3) Place the composite powder obtained in step (2) into a drying oven and dry it; (4) Place the dried composite powder from step (3) into a metal additive manufacturing equipment to form a sample; (5) Heat treat the molded sample obtained in step (4); In step (2), the mill speed is 70-90 rpm, the milling time is 6 hours, and the powder jar is vibrated for 10-15 minutes every 1-2 hours; In step (3), the drying oven is evacuated, the drying temperature is 60℃~80℃, and the drying time is 3~6 hours; In step (4), the substrate used for laser selective melting and forming is an aluminum alloy substrate. The substrate preheating temperature is 180-200°C, the scanning angle of adjacent powder layers is rotated by 67°, and argon gas is used in the forming chamber with an oxygen content of less than 100ppm. The heat treatment process in step (5) is a strengthening solution treatment and a re-aging treatment. The strengthening solution treatment is: 460℃~490℃, holding for 60~90min, heating to 480~510℃ at 5-10℃ / h, water quenching to room temperature, and transfer time <10s; pre-aging temperature 115~125℃, aging time 20~24h; re-aging temperature 150~200℃, aging time 20~24h; re-aging temperature 115~125℃, aging time 20~24h.

Citation Information

Patent Citations

  • In-situ preparation method of laser additive manufacturing aluminum alloy and product of in-situ preparation method

    CN107812941A

  • High-performance 7050 aluminum alloy 3D printing selective laser melting forming part and application thereof

    CN110449578A

  • High-strength aluminum alloys for structural applications, which are processable by additive manufacturing

    WO2021198231A1